Case report: Synchronous bladder and retroperitoneal paragangliomas: an extremely rare entity - Huang, Weitao; Liu, Yiming; Zhou, Miaoping (Frontiers in Oncology, 2025)
Paragangliomas (PGLs) are rare neuroendocrine tumors originating from chromaffin cells. The synchronous occurrence of bladder and retroperitoneal PGLs is extremely rare. This case highlights the radiological features of dual-site PGLs and their potential for misdiagnosis as bladder cancer with retroperitoneal lymph node metastasis. A 59-year-old female patient was admitted with a 2-week history of abdominal distention. Imaging showed a highly vascularized 1.3 cm × 1.2 cm nodule on the right wall of the bladder and a retroperitoneal mass measuring 1.8 cm × 3.7 cm adjacent to the left side of the abdominal aorta. Postoperative pathological examination confirmed dual-site PGLs. The multifocal appearance and hypervascular characteristics of these tumors may lead to misdiagnosis as bladder cancer with metastasis. Recognizing the clinical, imaging (such as CT and MRI findings), and pathological features is crucial for avoiding misdiagnosis and formulating an appropriate treatment plan.